COMBINATION STRATEGY AND ORGANIZATIONAL PERFORMANCE: BANKING INDUSTRIES IN VAVUNIYA DISTRICT, SRI LANKA - Pushpanathan, A. (Rajiv Academy for Technology and Manaement, Mathura, India, 2009)
Combination strategy is to be viable over the long run, and in many cases, to be associated with superior performance. In general, it was suggested that businesses successfully combining low costs and differentiation utilized synergies to overcome any tradeoffs that may be associated with the combination. Hence combination generic strategy may create a competitive advantage may be especially true for retailers. This study explores the combination strategy organizational performance: Banking industries in Vavuniya district. This study utilized data from 30 employees and 30 customers in banking industries. The relationship between differentiation strategy, cost leadership strategy, and combination strategy, and organizational performance were discussed in this study. The hypotheses were tested through the regression analysis using SPSS package. The results indicated that combination strategy was directly linked to organizational performance.
Keywords: Differentiation; Cost Leadership; Combination Strategy; Performance